The Influence of Physical Work Environment, Leadership Style and Work Stress on Employee Performance at PT. Uniplastindo Interbuana Ciawi Plant - Sakirin, Ahmad; Sudarijati; Pramestidewi, Chandra Ayu (MultiTech Publisher, 2024)
The importance of human resources in an organization or company is to determine the success of the organization or company in achieving its goals, because whether or not a company is successful in achieving its goals really depends on the ability of its human resources or employees in carrying out the tasks assigned to them.This research aims to analyze and identify the influence of the physical work environment, leadership style and work stress simultaneously and partially on employee performance. The analytical method used in this research is a descriptive method, multiple linear regression analysis with a quantitative approach and sampling from 74 respondents. The results of the research show that 1) the physical work environment, leadership style and work stress simultaneously have a positive and significant effect on employee performance. 2) the physical work environment, work stress and leadership style partially have a positive and significant effect on employee performance.